Dukungan Keluarga dan Kepatuhan Diet pada Penderita Hipertensi di Wilayah Kerja Puskesmas Cangkringan Sleman Yogyakarta - Kardiyudiani, Ni Ketut; Nurwidiyanti, Erika; Djabir, Wani (Penerbit Goodwood, 2024)
Purpose: To identify family support and dietary compliance in patients and analyze the correlation between family support and dietary adherence in patients with hypertension in the Cangkringan Sleman Yogyakarta Community Health Center. Methods: This study used a descriptive correlation with a cross-sectional approach. The sample consisted of 30 hypertensive patients who underwent total sampling. Data were collected using a questionnaire on family support and hypertension diet compliance, which was tested for validity and reliability. Data analysis was performed using the Spearman’s rank correlation test. Results: Most respondents had family support in the sufficient category (73,33%), and dietary compliance in the poor category (80,0%). There was a significant moderate correlation between family support and dietary compliance in patients with hypertension, with a p-value of 0,007 (< 0,05) with a moderate correlation. Limitations: There was a significant correlation between family support and dietary compliance in hypertensive patients. Health workers, especially nurses, are expected to be able to improve health services for patients with hypertension by involving families, especially in contribution, which is a silent disease that can cause various complications such as coronary heart disease and rupture of cerebral blood vessels, resulting in paralysis and even death. Contribution: Patients with hypertension must adhere to a diet throughout their lives, which requires strong motivation and commitment from within the sufferer. Family support is important for patients’ compliance with dietary recommendations.